Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1073/pnas.95.25.14891
|View full text |Cite
|
Sign up to set email alerts
|

Gene dosage and stochastic effects determine the severity and direction of uniparental ribosomal RNA gene silencing (nucleolar dominance) in Arabidopsis allopolyploids

Abstract: Nucleolar dominance is an epigenetic phenomenon in which one parental set of ribosomal RNA (rRNA) genes is silenced in an interspecific hybrid. In natural Arabidopsis suecica, an allotetraploid (amphidiploid) hybrid of Arabidopsis thaliana and Cardaminopsis arenosa, the A. thaliana rRNA genes are repressed. Interestingly, A. thaliana rRNA gene silencing is variable in synthetic Arabidopsis suecica F 1 hybrids. Two generations are needed for A. thaliana rRNA genes to be silenced in all lines, revealing a specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
169
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(182 citation statements)
references
References 46 publications
8
169
1
2
Order By: Relevance
“…Moreover, the demonstration that underdominant rRNA genes are abundantly expressed in Arabidopsis and Brassica upon blocking DNA methylation or histone deacetylation, and dominant genes are also up-regulated, suggests that transcription factors are present in sufficient amounts to support very high levels of transcription provided that the genes are in an accessible chromatin state [39,40,46]. The demonstration that the direction of nucleolar dominance can be reversed in response to changes in ploidy in Arabidopsis thaliana x A. arenosa hybrids bearing 1:3, 2:2 or 3:1 genome dosages of the two progenitors [43] also does not fit with the idea that one parental type of rRNA gene has an inherently higher binding affinty for a limiting transcription factor, in which case that gene type would always recruit transcription factors and be transcribed to some degree. There is no correlation between intergenic spacer length or repeat number in Brassica allotetraploids that display nucleolar dominance [76].…”
Section: Are Nors Regulated As Single Loci or Is It Every Rrna Gene mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the demonstration that underdominant rRNA genes are abundantly expressed in Arabidopsis and Brassica upon blocking DNA methylation or histone deacetylation, and dominant genes are also up-regulated, suggests that transcription factors are present in sufficient amounts to support very high levels of transcription provided that the genes are in an accessible chromatin state [39,40,46]. The demonstration that the direction of nucleolar dominance can be reversed in response to changes in ploidy in Arabidopsis thaliana x A. arenosa hybrids bearing 1:3, 2:2 or 3:1 genome dosages of the two progenitors [43] also does not fit with the idea that one parental type of rRNA gene has an inherently higher binding affinty for a limiting transcription factor, in which case that gene type would always recruit transcription factors and be transcribed to some degree. There is no correlation between intergenic spacer length or repeat number in Brassica allotetraploids that display nucleolar dominance [76].…”
Section: Are Nors Regulated As Single Loci or Is It Every Rrna Gene mentioning
confidence: 99%
“…Foremost of these is the fact that a ten million fold excess of rRNA minigenes is typically injected relative to the number of endogenous rRNA genes, which may artificially create transcription factor deficiencies that endogenous rRNA genes never experience. Analogous tests in plants in which minigenes were transfected into protoplasts in numbers similar to the number of endogenous rRNA genes failed to reveal any differences in the competitive strength of dominant and underdominant genes, nor did competitive in vitro transcription assays [43,86]. Moreover, the demonstration that underdominant rRNA genes are abundantly expressed in Arabidopsis and Brassica upon blocking DNA methylation or histone deacetylation, and dominant genes are also up-regulated, suggests that transcription factors are present in sufficient amounts to support very high levels of transcription provided that the genes are in an accessible chromatin state [39,40,46].…”
Section: Are Nors Regulated As Single Loci or Is It Every Rrna Gene mentioning
confidence: 99%
See 1 more Smart Citation
“…(77) However, in Arabidopsis and Brassica allotetraploids, differential rRNA gene expression is not associated with enhancers or availability of species-specific transcription factors. (78,79) Transient and in vitro transcription assays have shown that Arabidopsis and Brassica rRNA promoters can function with the RNA Polymerase I transcription machinery of the other species. (78,80) Silenced rRNA genes in Arabidopsis and Brassica allotetraploids were reactivated by chemical inhibitors for DNA methylation and/or histone deacetylation, suggesting that rRNA genes are silenced by DNA and histone modifications presumably associated with inactive chromatin structure.…”
Section: Activation Of Transposons and Changes In Dna Methylation In mentioning
confidence: 99%
“…(43,79) For some genes, including rRNA genes, it takes 1-2 generations to establish a differential expression (silencing or activation) pattern. For others, it takes more than two and sometimes five generations to establish expression status.…”
Section: Activation Of Transposons and Changes In Dna Methylation In mentioning
confidence: 99%